Optimal Harvesting Strategy of a Discretization Fractional-Order Biological Model - Al-Nassir, Sadiq (Iraqi Journal of Science, 2022)
Optimal control methods are used to get an optimal policy for harvesting renewable resources. In particular, we investigate a discretization fractional-order biological model, as well as its behavior through its fixed points, is analyzed. We also employ the maximal Pontryagin principle to obtain the optimal solutions. Finally, numerical results confirm our theoretical outcomes.